Perfil epidemiológico e de saúde mental das tentativas de suicídio de Francisco Beltrão - PR, de 2017 à 2020 - Biezus, Aline Marieli Jochem (2021)
Suicide has become a major Public Health problem in all countries, as it is a complex phenomenon that can result from a set of interactions of multifactorial causes. It is the third leading cause of death in the world and Brazil is among the 10 countries with the highest rates of notified cases. Studies in different regions of the world have shown that almost all suicides involve individuals who were suffering from a mental disorder, and that suicidal behavior is more frequent in psychiatric patients with a history of previous suicide attempts. Thus, the aim of this study was to investigate and analyze the epidemiological profile and correlation with mental disorders in cases of suicide attempts in the city of Francisco Beltrão, Paraná. To carry out this work, a descriptive/quantitative epidemiological study of suicide attempts that occurred in the city of Francisco Beltrão, between 2017 and 2020 was carried out. , and subsequent assessment of the electronic medical records of these patients. Absolute and relative frequencies were calculated and used to describe the sample profile. To compare the variants, the chi-square test was performed, with values that presented p <0.05 being considered statistically significant. Of the 447 notifications, 382 were eligible for the survey. There was a higher percentage of females, aged under 35 years, white race/color, single and with a history of repeated attempts, using exogenous intoxication as the main method. It was shown, with the greatest frequency, that the patients suffered from some diagnosis of mental disorder, being the recurrent depressive disorder with the highest prevalence. Finally, the data obtained reveal that there is an urgent need for the implementation of preventive measures aimed, especially in populations with a history of suicide attempts, mental disorders, and females.